2014
DOI: 10.1111/acem.12377
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Children With Suspected Appendicitis and Incompletely Visualized Appendix on Ultrasound

Abstract: Objectives: The objective was to review the clinical outcomes of children with suspected appendicitis after an ultrasound (US) examination fails to fully visualize the appendix, the diagnostic characteristics of US in children with suspected appendicitis, and the predictive value of secondary signs of appendicitis when the appendix is not fully visualized.Methods: This was a retrospective health record review of children aged 3 to 17 years presenting to a tertiary pediatric emergency department (ED) with suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 20 publications
1
46
0
2
Order By: Relevance
“…Reliance on secondary signs however has also been associated with a high number of false positives 4. Estey et al53 and more recently Ross et al54 confirmed the PPV of secondary signs, yet their absence did not permit reliable exclusion of appendicitis. These contradictory findings warrant further investigation to determine the diagnostic potential of individual or certain combinations of secondary signs to obtain the most comprehensive and meaningful sonographic conclusion.…”
Section: Methodsmentioning
confidence: 99%
“…Reliance on secondary signs however has also been associated with a high number of false positives 4. Estey et al53 and more recently Ross et al54 confirmed the PPV of secondary signs, yet their absence did not permit reliable exclusion of appendicitis. These contradictory findings warrant further investigation to determine the diagnostic potential of individual or certain combinations of secondary signs to obtain the most comprehensive and meaningful sonographic conclusion.…”
Section: Methodsmentioning
confidence: 99%
“…We performed a retrospective health record review, combining data that were available from a study previously reported by our team 9 with US images to calculate bladder size. This study was approved by the Conjoint Health Research Ethics Board of the University of Calgary.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline demographic and clinical data were available from our previously published health record review, 9 in which we collected demographic data, ED visit details, results of laboratory investigations, surgical considerations, frequency of return visits to the ED, and imaging reports. These data were used in a previous study 9 to examine the outcomes of children with suspected appendicitis after US examination failed to identify the appendix.…”
Section: Study Protocolmentioning
confidence: 99%
See 2 more Smart Citations